2016
DOI: 10.1093/jrs/few025
|View full text |Cite
|
Sign up to set email alerts
|

‘Barahunga Amahoro—They Are Fleeing Peace!’ The Politics of Re-Displacement and Entrenchment in Post-War Burundi

Abstract: Ahead of the 2015 contested elections, Burundi got embroiled in a vast refugee crisis only a decade after the end of the civil war. Against the official government efforts to depoliticize the crisis, the paper draws on interviews with Burundians across space and time to underscore the fundamentally political character of migration decisions after the war, and argues for the applicability of the social contract theory for a bottom-up conception of political incorporation and citizenship. The evidence suggests t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Moreover, in respect to the 2015 new wave of forced displacement, humanitarian organisations have reported that a large number of Burundian refugees have yet to return, which implies that many refugees would consider a return to be a choice rather than a necessity [64]. In the current situation where the delay to file claims on pre-displacement land to the CNTB has passed, we anticipate that most Burundian refugees might not return to their places of origin.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, in respect to the 2015 new wave of forced displacement, humanitarian organisations have reported that a large number of Burundian refugees have yet to return, which implies that many refugees would consider a return to be a choice rather than a necessity [64]. In the current situation where the delay to file claims on pre-displacement land to the CNTB has passed, we anticipate that most Burundian refugees might not return to their places of origin.…”
Section: Discussionmentioning
confidence: 97%
“…Despite a strong presence of the state in local communities, dispute resolution processes that aimed at land and property restitution have been contested either overtly or discreetly at the community level. Land restitution remains a critical, complex and highly politically sensitive and possibly destabilising issue in Burundi [13,64]. However, state control over local restitution dynamics has increased, because of subsequent policy and legal changes, and the massive return of refugees.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, he fled to Tanzania with nearly 200,000 other Burundians to escape the political crisis that resulted in widescale protests, an attempted coup and state‐sponsored repression when Burundian President Pierre Nkurunziza overstayed his two‐term limit established after the Burundian civil war. Victor, like most others, had already lived as a refugee in Tanzania during the war but struggled to reintegrate upon returning to Burundi without safe access to land or livelihoods (Falisse and Niyonkuru, 2015; Purdeková, 2017; Schwartz, 2019). Dalia is a Congolese woman who fled South Kivu province in 1996 due to violence during the First Congolese War.…”
Section: Introductionmentioning
confidence: 99%
“…With a demographic pressure of over 350 inhabitants per square kilometre, and more than 90% of the population involved in subsistence farming, land constitutes a key determinant of local livelihoods, social status, identity and belonging in Burundi. Post-independence ethnopolitical turmoil, violence, and displacement have contributed to widespread tenure insecurity and land disputes (International Crisis Group, 2003;Kohlhagen, 2012;Purdeková, 2016;Sinarinzi and Nisabwe, 1999;Zeender and McCallin, 2013). This paper focuses on claim-making to land in settings where multiple waves of (forced) displacement and (partial) return have led to overlapping, competing claims that lead to tensions and animosity at the local level.…”
Section: Introductionmentioning
confidence: 99%